A Canadian experience of palliative advanced practice radiation therapy TIPS: Training, implementation, practice and sustainability. (March 2021) - Rozanec, Natalie; Lavergne, Carrie; Harnett, Nicole
Abstract: The concept of the Advanced Practice Radiation Therapist (APRT) was created in 2004, in response to pressures on the radiation treatment sector in Ontario. This led to development, piloting and integration of the Clinical Specialist Radiation Therapist (CSRT) into Ontario's cancer care framework. A national certification process, competency profile and protected title of APRT(T) were established in 2017, under the Canadian Association of Medical Radiation Technologists (CAMRT), in collaboration with Cancer Care Ontario/Ontario Health. This report describes the approach to development, validation and measuring impact of the CSRT role in Ontario, specifically in palliative care (pCSRT). It also presents information to assist jurisdictions interested in developing a pCSRT position, describing competency development, assessment, and assumption of practice, and providing some keys to success. This is foundational for consistent expansion of the pCSRT role to other regions to continue to increase system capacity while improving the quality of cancer care.